Perbandingan Pengaruh Komite Audit Terhadap CSR Di Perusahaan Publik (Studi Komparasi: Negara Indonesia Dan Malaysia) - Eni Kaharti (Universitas Veteran Bangun Nusantara, 2022)
This study aims to compare the influence of audit committees on CSR carried out by public companies listed on the stock exchange before and during the Covid-19 pandemic. The sub-sectors used are finance, food and real estate. The data used are secondary data for 2019 and 2020. What is being tested is the effect of audit committees on comparative CSR in two countries, namely Indonesia and Malaysia in 2019 and 2020. The amount of data used by Indonesia is the finance sector (198 companies), food ( 46 companies), and property ( 92 companies) a total of 336 companies. For Malaysia, the finance sector (56 companies), food (48 companies), and property 172 (companies), a total of 276 companies. Variable X (Audit Committee) Variable Y (CSR), Control Variables used are profitability and liquidity. During normal times and during endemic cofid 19 adutit committees in Indonesia and Malaysia both had a positive and significant effect on CSR. The research was only conducted on certain companies (finance, food and property), not all companies listed on the Indonesian and Malaysian Stock Exchanges. This study specifically examines and compares the influence of audit committees on CSR in normal and pandemic times in two countries, Indonesia and Malaysia. Keywords: Audit Committee, CSR